Familial reactive perforating collagenosis in two siblings - Abhijna K Rai; Mamatha S Kusagur; K S Chandan (Wolters Kluwer Medknow Publications, 2018)
Reactive perforating collagenosis (RPC) is a rare form of transepithelial elimination disorder, in which genetically altered collagen is extruded through the epidermis. Of the acquired and inherited form, the latter is extremely rare. Here, we present two cases of inherited form of RPC in siblings aged 4 and 7 years presented with a history of itchy raised lesions of 9 months and 3 years duration, respectively. Dermatological examination revealed multiple papules with a central keratotic plug distributed mainly over face and extensors of upper and lower extremities. Köebnerization was present. Skin biopsy revealed perforating collagen bundles in the upper dermis and epidermis.